Similarities and Differences between Coronavirus Disease 2019-related Multisystem Inflammatory Syndrome in Children and Kawasaki Disease in Indian Patients - Utkarsh Singh; Suhas Prabhu; Deepak Phalgune (Pediatric Infectious Disease)
Background: There is a marked overlap of clinical and laboratory features of multisystem inflammatory syndrome in children (MIS-C) and Kawasaki disease (KD); resulting in a diagnostic dilemma. Studies comparing MIS-C and KD in Indian children are limited. The present study was conducted to describe the similarities and differences between MIS-C and KD which may help in diagnosis. Materials and methods: This prospective observational and retrospective study was conducted between April 2022 and March 2023. A total of 82 children <18 years of age were included; 41 with MIS-C and 41 diagnosed as KD admitted in the same hospital as controls. The primary objectives were to compare the gastrointestinal manifestations between the two groups, whereas the secondary objectives were to compare the mucocutaneous and cardiac manifestations. Results: The mean duration of fever was significantly longer in children with KD compared to those with MIS-C. Gastrointestinal manifestations were notably more prevalent in the MIS-C group, whereas mucocutaneous signs were more frequently observed in the KD group (KDG). Evidence of shock, the use of inotropes, and the need for respiratory support were significantly higher in the MIS-C group than in the KDG. Myocardial dysfunction and pericardial effusion/regurgitation were also more prevalent in the MIS-C group, whereas coronary dilatation/aneurysm was significantly lower compared to the KDG. Mean white blood cell (WBC) count, percentage of lymphocytes, absolute lymphocyte count (ALC), and platelet count were notably higher in the KDG compared to the MIS-C group. Liver function tests (LFTs), renal function tests (RFTs), and inflammatory markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were comparable between the two groups. Conclusion: There were vast similarities between KD and MIS-C, suggesting that they lie along the same clinical spectrum. However, there are several differences between the two disease entities.